Features of digital strategies of small and medium-sized enterprises in the fmcg market ("Journal "U". Economy. Management. Finance.", 2022)
In this article, the author examines the features of digital strategies of small and medium-sized enterprises in the market of consumer goods. The author emphasizes that the use of digital marketing as an effective means of communication has contributed to the integration of technologies into the collection of massive customer data that is valuable for organizations when making decisions. This article is aimed at studying the factors influencing the adoption of digital marketing by small and medium-sized enterprises in the consumer goods market. The data obtained show that the factors influencing the adoption of digital marketing by small and medium-sized enterprises are the perceived advantages over the use of digital marketing, its adoption as a means of communication with customers and the experience of using it. It was also found that this business segment mainly uses social networks and email marketing as digital marketing tools to get closer to its customers.
Keywords: digital marketing; business; SMEs; electronic market; FMCG; small and medium enterprises